Protein nutrition governs within-host race of honey bee pathogens. Issue 1 (December 2017) - Tritschler, Manuel; Vollmann, Jutta; Yañez, Orlando; Chejanovsky, Nor; Crailsheim, Karl; Neumann, Peter
Abstract Multiple infections are common in honey bees, Apis mellifera, but the possible role of nutrition in this regard is poorly understood. Microsporidian infections, which are promoted by protein-fed, can negatively correlate with virus infections, but the role of protein nutrition for the microsporidian-virus interface is unknown. Here, we challenged naturally deformed wing virus - B (DWV-B) infected adult honey bee workers fed with or without pollen ( = protein) in hoarding cages, with the microsporidianNosema ceranae . Bee mortality was recorded for 14 days andN. ceranae spore loads and DWV-B titers were quantified. Amongst the groups inoculated withN. ceranae, more spores were counted in protein-fed bees. However, N. ceranae infected bees without protein-diet had reduced longevity compared to all other groups.N. ceranae infection had no effect on protein-fed bee's longevity, whereas bees supplied only with sugar-water showed reduced survival. Our data also support that protein-feeding can have a significant negative impact on virus infections in insects. The negative correlation betweenN. ceranae spore loads and DWV-B titers was stronger expressed in protein-fed hosts. Proteins not only enhance survival of infected hosts, but also significantly shape the microsporidian-virus interface, probably due to increased spore production and enhanced host immunity.